2-Iodo-N-isopropyl-5-methoxybenzamide as a highly reactive and environmentally benign catalyst for alcohol oxidation - Yakura, Takayuki; Fujiwara, Tomoya; Yamada, Akihiro; Nambu, Hisanori (Beilstein Journal of Organic Chemistry, 2018)
Several N-isopropyliodobenzamides were evaluated as catalysts for the oxidation of benzhydrol to benzophenone in the presence of Oxone® (2KHSO5·KHSO4·K2SO4) as a co-oxidant at room temperature. A study on the substituent effect of the benzene ring of N-isopropyl-2-iodobenzamide on the oxidation revealed that its reactivity increased in the following order of substitution: 5-NO2 < 5-CO2Me, 3-OMe < 5-OAc < 5-Cl < H, 4-OMe < 5-Me < 5-OMe. The oxidation of various benzylic and aliphatic alcohols using a catalytic amount of the most reactive 5-methoxy derivative successfully resulted in moderate to excellent yields of the corresponding carbonyl compounds. The high reactivity of the 5-methoxy derivative at room temperature is a result of the rapid generation of the pentavalent species from the trivalent species during the reaction. 5-Methoxy-2-iodobenzamide would be an efficient and environmentally benign catalyst for the oxidation of alcohols, especially benzylic alcohols.
Keywords: hypervalent iodine; iodobenzamide; organic catalysis; oxidation; oxone